(untitled) (Research, Society and Development, 2022)
Objetivo: comprender el mundo de vida de los enfermeros frente a las dificultades y desafíos en el prenatal de alto riesgo.Methodology: a qualitative study with a phenomenological approach, using Alfred Schütz’s comprehensive sociology as a methodological theoretical support. The study development scenarios were the four referral outpatient clinics for high-risk prenatal care in Alagoas: Hospital Universitário Professor Alberto Antunes, in Maceió; Santa Monica Maternity School, in Maceió; Espaço Nascer, in Arapiraca; and the Quitéria Neves Women’s Health Care Center, in Santana do Ipanema.The study included seven nurses who provide care to pregnant women in high-risk prenatal clinics in Alagoas. Open interviews were carried out at the place where each of the nurses worked, guided by the following triggering question: “What is the experience of working as a nurse assisting pregnant women who are at high risk during prenatal care for you?Results: the thematic category emerged from the testimonies: life world of nurses facing difficulties and challenges to work in high-risk prenatal care.Conclusion: the analyzed data allowed identifying the assistance performed by nurses in the care of pregnant women, in high-risk prenatal care in Alagoas, through the identification of the "reasons why" and "reasons for" this professional action and the subjects’ statements, revealing the difficulties and challenges faced by these nurses in their life world.